THE EXPORT COMPETITIVENESS OF SOCIAL ENTERPRISES AS COMPARED TO WITH EXPORT SMES - GUTIÉRREZ FERNÁNDEZ, Arturo; PÉREZ-SUÁREZ, Macarena (Revista Galega de Economía, 2017)
Purpose – This study aims to determine the export competitiveness of the Social Economy in Andalusia, this is carried out by quantifying the export competitiveness of the internationalized enterprises of the Social Economy in the export sector of the region. Design/methodology/approach – The strengths and weaknesses of this business sector are quantified and the Rasch´s Probability. It is a model used to measure the latent variable called export competitiveness, which is defined by items (factors): size, cooperation, number of target markets, competitive advantages, years abroad and percentage of sales abroad. The article provides empirical evidence of 362 Andalusian export enterprises. Findings – The results show that the export competitiveness of social enterprises reflected their strengths as compared with other SMEs. Originality/value – This concept paper empirically combines two different fields of knowledge (design and behavior of companies) in the construction of the foreign trade. This work standardizes the treatment of two descriptors scarcely discussed in the literature: Social Enterprises and Export.